UPAYA MENINGKATKAN KEMAMPUAN PESERTA DIDIK MENULIS TEKS DESCRIPTIVE MATA PELAJARAN BAHASA INGGRIS MENGGUNAKAN MODEL MIND MAPPING - AFRIANTI, NINA (Jurnal Tunas Pendidikan, 2020)
This research is motivated by the number of students as many as 23 class VII.1 State Junior High School 5 Muara Bungo in English language writing descriptive text, the number of students who have not met the KKM as many as 19 people (83%). This is still below the Minimum Mastery Criteria (KKM) set by schools 69.The research used the Classroom Action Research approach which was carried out in class VII.1 of SMP Negeri 5 Muara Bungo in the Academic Year of 2017/2018 with 23 students and assisted by research partners. PTK includes two cycles, namely Cycle I and Cycle II. One of the performance indicators used as a reference in determining the success of each CAR is a Minimum completeness criteria (KKM) determined with a value of 69. A learning process is successful if the minimum number of students who meet the minimum KKM is 75% of the total students. Other indicators increase the performance of the learning process with an increasingly mind map model, which is valued by the research partners and students behaving better and better in each cycle.The results of this PTK study show the hypothesis in this CAR, namely: "The use of mind mapping learning models can improve the ability of students of class VII.1 Middle School 5 Muara Bungo 2017/2018 Academic Year in writing descriptive English text" can be accepted. The number of students who met the KKM pre cycle 17% the remaining 83% did not meet the KKM. In the first cycle to 26% the number of students who met the KKM the remaining 74% did not meet the KKM. In the second cycle 91% of the number of students who met the KKM did not meet the KKM 9%. The number that meets the KKM in the second cycle has reached 75% as the standard of success for each cycle.